Um conjunto de faianças da Vila de Alcoutim - Gradim, Alexandra (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This study presents a group of faiences from the village of Alcoutim. The chosen collection was found in a noble modern house and contributes to new information to knowledge of dating and classification of tin-glazed earthenware. Typologies for the forms and decoration of these 15th until 18th even 19th century ceramics, produced in Portugal or imported from Spain and Italy, are presented.